2019
DOI: 10.1590/0102-311x00170218
|View full text |Cite
|
Sign up to set email alerts
|

Adaptação transcultural e validação do Questionário de Atitudes Socioculturais em Relação à Aparência-4 (SATAQ-4) aplicado a estudantes universitários

Abstract: Resumo: O objetivo deste estudo foi traduzir e adaptar culturalmente o Questionário de Atitudes Socioculturais em Relação à Aparência-4 (SATAQ-4) para a língua portuguesa e avaliar sua validade e confiabilidade quando aplicado a estudantes brasileiros. Realizou-se a validação de face, de conteúdo e pré-teste. Para a avaliação do índice de incompreensão, participaram do pré-teste 91 estudantes de três países de língua portuguesa (25 brasileiros, 37 portugueses e 29 moçambicanos). A validade de construto foi est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Analysis of CFA in women demonstrated that according to most fit indices, data fit fairly well. These results are consistent with previous psychometric evaluations of the SATAQ-4 in nationally different female samples [14][15][16][17]. As expected, for men, the model demonstrated unacceptable model fit values.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Analysis of CFA in women demonstrated that according to most fit indices, data fit fairly well. These results are consistent with previous psychometric evaluations of the SATAQ-4 in nationally different female samples [14][15][16][17]. As expected, for men, the model demonstrated unacceptable model fit values.…”
Section: Discussionsupporting
confidence: 91%
“…The Sociocultural Attitudes Towards Appearance Questionnaire-4 (SATAQ-4) is one of the most broadly used self-report tools that assess the general role of sociocultural influences on body image and appearance-related internalization [14]. To date, SATAQ-4 has been validated in Italian, Spanish, Portuguese, English, France, Australian, and Japanese samples of young men and women [15][16][17][18] and has demonstrated strong psychometric properties.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, concerning the quality of the studies, it is evident that 12 of them (85.7%) had scores above the pre-established average of 50%, which indicates that these articles were of good quality (Amaral et al, 2011 ; Barra et al, 2019 ; Bas et al, 2017 ; Campana et al, 2013 ; Carbonneau et al, 2016 ; Chakroun-Baggioni et al, 2017 ; Conti et al, 2012 ; Pakpour et al, 2014 ; Rousseau et al, 2014 ; Shoji et al, 2018 ; Silva et al, 2016 ; Ulian et al, 2017 ). As for the remaining percentage, two articles (14.2%) scored exactly the previously determined average, indicating acceptable quality (Conti et al, 2010 ; de Carvalho et al, 2013 ).…”
Section: Resultsmentioning
confidence: 96%
“…Although these values are recognized in the literature, some studies did not achieve them. For example, Barra et al ( 2019 ) presented χ 2 /gl = 8.39; Rousseau et al ( 2014 ) reported the following AGFI values = 0.82; GFI = 0.86, and Pakpour et al ( 2014 ) highlighted GFI = 0.86, NFI = 0.84, CFI = 0.85. RMSEA values that did not fit the reference standard were also found, as example RMSEA = 0.191 (Pakpour et al, 2014 ) and RMSEA = 0.09 (Chakroun-Baggioni et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation